PENGARUH VARIASI WAKTU KONTAK PADA METODE ELEKTROKOAGULASI DALAM PENGOLAHAN LIMBAH CAIR BATUBARA - Hidayati, Syifa Yulia; Alim, Muhammad Syahirul (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2025)
Coal wastewater can be treated by electrocoagulation method, is wastewater treatment using direct electricity and electrodes Aluminum (Al) plates. An analysis of the results of the quality test of coal effluent was carried out after the electrocoagulation method was carried out in meeting environmental quality standards according to the Peraturan Gubernur Kalimantan Selatan No. 36 Tahun 2008 tentang Baku Mutu Air Limbah Batubara and analysis of the effect of the contact time used, namely 30, 45, 60, 75 and 90 minutes. The research method used is the experimental method. The parameters tested were Total Suspended Solid (TSS), pH, iron (Fe) and manganese (Mn) and the distance between the electrode plates was 1 cm. The voltage used 12 volts. The results showed that at a contact time of 90 minutes the electrocoagulation process was effective in reducing contaminants so that it met quality standards, the TSS parameter value of efficiency reached 99.97% with a decrease in levels from 4305 mg/L to 1.33 mg/L, on the parameter pH increased from 5.37 to 7.27, in the iron (Fe) parameter the efficiency value reached 99.96% with a decrease in levels from 53 mg/L to 0.02 mg/L and the manganese (Mn) value efficiency reached 99.81% with a decrease in levels from 20.32 mg/L to 0.039%.